Experimental and numerical analyses of the ultimate compressive strength of perforated offshore tubular members - Vaz, Murilo A.; Cyrino, Julio C.R.; Hernández, Irving D.; Zegarra, Victor D.; Martinez, Jorge L.; Liang, Denis A. (Marine structures, 2018)
Tubular steel members are widely used as structural elements in offshore units. The strength capacity and design formulas for intact members, subject to axial compressive forces, have been thoroughly investigated. However, there are few studies on the behavior of perforated tubular members from offshore aged units and on their remaining load capacity assessment. Perforation damage leads to deterioration of strength capacity and life-time shortening of the structures. The aim of this paper is to present an experimental campaign and a numerical finite element model to obtain the ultimate strength of tubular structures with circular perforated damage subjected to axial compression. In the experimental program fifteen tubular scaled specimens are tested and results are compared with the ones from geometrical and material non-linear finite element model considering reconstructed geometries, variable thickness distribution and actual material stress-strain curves. Shell elements are used and the finite element meshes are obtained from detailed external wall 3D laser scanning of the experimental samples and ultrasonic thickness measurements in several cross-sections. Spatial thickness interpolation is performed to define the thickness in all meshed nodes. Results from numerical model analyses demonstrate considerable accuracy and good agreement with those directly measured from experimental perforated tubular member's samples in terms of axial load-displacement and strains. From the results, it has been concluded that the perforation size is the most important variable in determining the extent of the compressive strength degradation. •An experimental apparatus is constructed to apply compressive loads in scaled tubular elements typical of flare booms.•Material tests, wall thickness, and geometrical imperfections are measured.•15 samples are tested, ranging from length to diameter ratios from 7 to 40.•Intact and perforated samples are tested, with the objective of obtaining their remaining capacity.•A Finite Element Model is developed and results are compared with the ones from experiments.